In vitro screening of Capparishorrida L. pericarp for antimicrobial and anticancer activity - KRISHNAVENI,; SANGEETHA, (International Journal of Pharma and Bio Sciences, 2018)
Capparishorrida is commonly known as Indian caper, found in India, Bangladesh, Sri Lanka, Malaysia and some parts of Pakistan. Capparishorrida belongs to the family Cappareaceae. Almost all the parts of the plant are used for different medicinal purposes and it is used in many ayurvedic formulations. The aim of the present study is to characterize the phytochemical, antibacterial and in vitro anticancer activity of Capparishorrida stem extracts. Qualitative phytochemical screening tests were done using ethyl acetate, hexane and water stem extracts of Capparishorrida. Antibacterial activity of stem bark extracts of Capparishorrida was determined by agar well diffusion method. In vitro antiproliferative activity of Capparishorrida against PA-1 (ovarian cell line) was determined using MTT assay. In vitro cytotoxic activity by MTT assay against L929 (fibroblast cell line) was also analysed. Preliminary phytochemical screening of ethylacetate, hexane and water extracts of Capparishorrida stem revealed the presence of alkaloids, terpenoids and flavonoids. The observed inhibitory potential of the extracts towards bacteria and cancer cells could be ascribed to the presence of these secondary metabolites in the extracts.